Managerial strategies and practice in the Asian business sector - Zeyar Myo Aung, U, 1973-; d; IGI eBooks; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA) : IGI Global, 2016)
"This book is a comprehensive reference source for theories and practices related to business integration in Asian countries"--Provided by publisher.
Promoting leadership development and talent management in modern organizations / Kijpokin Kasemsap -- The role of gold market as stabilizer of service industry / Heliang Zhu, Xi Zhang, Patricia Ordenaz de Pablos -- What attracts foreign direct investments in Asian economies?: an institutional approach to FDI / Hironori Tohyama -- Youth entrepreneurship in India: outlook and obstacle / Neeta Baporikar.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 01/13/2016).
Keywords: Management -- Asia; Asian business; Asian economics; Economic development; Entrepreneurship; Globalization; Social development; Sustainable business; Tourism; Electronic books